Hand and Grasp Selection in a Preferential Reaching Task: The Effects of Object Location, Orientation, and Task Intention - Scharoun, Sara M.; Scanlan, Kelly A.; Bryden, Pamela J. (Frontiers in Psychology, 2016)
As numerous movement options are available in reaching and grasping, of particular interest are what factors influence an individual’s choice of action. In the current study a preferential reaching task was used to assess the propensity for right handers to select their preferred hand and grasp a coffee mug by the handle in both independent and joint action object manipulation contexts. Mug location (right-space, midline and left-space) and handle orientation (towards, away, to left and to right of the participant) varied in four tasks that differed as a function of intention: (1) pick-up (unimanual, independent); (2) pick-up and pour (bimanual, independent); (3) pick-up and pass (unimanual, joint action); and (4) pick-up, pour and pass (bimanual, joint action). In line with previous reports, a right-hand preference for unimanual tasks was observed. Furthermore, extending existing literature to a preferential reaching task, role differentiation between the hands in bimanual tasks (i.e., preferred hand mobilizing, non-preferred hand stabilizing) was displayed. Finally, right-hand selection was greatest in right space, albeit lower in bimanual tasks compared to what is typically reported in unimanual tasks. Findings are attributed to the desire to maximize biomechanical efficiency in reaching. Grasp postures were also observed to reflect consideration of efficiency. More specifically, within independent object manipulation (pick-up; pick-up and pour) participants only grasped the mug by the handle when it afforded a comfortable posture. Furthermore, in joint action (pick-up and pass; pick-up, pour and pass), the confederate was only offered the handle if the intended action of the confederate was similar or required less effort than that of the participant. Together, findings from the current study add to our knowledge of hand and grasp selection in unimanual and bimanual object manipulation, within the context of both independent and joint action tasks.